Obciążenia podatkowe a konkurencyjność przedsiębiorstw agrobiznesu po wstąpieniu Polski do Unii Europejskiej - Boratyńska, Katarzyna (Fiscal Burden and Agribusiness Enterprises Competitiveness after Polish EU Integration, 2006)
The purpose of this paper is to compare excise taxes imposed on beer and the VAT rates in Poland and the other EU countries. The author states that too high fiscal burdens are a significant factor limiting Polish breweries competitiveness. EU citizens may bring in 110 liters of beer, which is more by one third than the annual consumption per capita in Poland. Considering that the excise tax in Germany and the Czech Republic is about 9.5 euro per 100 liters, in Poland this rate is more than double. Moreover, Polish citizens can buy cheap beer in Germany or in the Czech Republic and bring it duty free to Poland. This can be dangerous for Polish breweries that are located near the border. According to the Association of Polish Regional Breweries the tax excise system is their major obstacle.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 103-109